2007
DOI: 10.2174/092986707781745578
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Factors - A Tool for Therapeutic Strategies in Neurological,Neuropsychiatric and Neuroimmunological Diseases?

Abstract: Nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) belong to the protein family of neurotrophins. They both display profound neuromodulatory functions and are essentially involved in the survival and homeostatic maintenance of central and peripheral neurons during development and adulthood. Moreover, NGF and BDNF are known to modulate immune cell function and thus serve as mediators in the reciprocal cross talk between neurons and immune cells. Neurotrophic factors have been implicated in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 196 publications
(235 reference statements)
0
54
0
Order By: Relevance
“…Neurotrophin nerve growth factor (NGF) contributes to cutaneous innervation development and turnover (Tominaga et al, 2009) and maintains SP þ nerve fibers in the skin (Botchkarev et al, 2004;Schulte-Herbruggen et al, 2007). It is also involved in stress-induced cutaneous hyperinnervation (Peters et al, 2007) and induces keratinocyte proliferation (Botchkarev et al, 2004), mast cell degranulation (Tal and Liberman, 1997), and alterations of the cytokine balance that promote allergic inflammation (Bonini et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotrophin nerve growth factor (NGF) contributes to cutaneous innervation development and turnover (Tominaga et al, 2009) and maintains SP þ nerve fibers in the skin (Botchkarev et al, 2004;Schulte-Herbruggen et al, 2007). It is also involved in stress-induced cutaneous hyperinnervation (Peters et al, 2007) and induces keratinocyte proliferation (Botchkarev et al, 2004), mast cell degranulation (Tal and Liberman, 1997), and alterations of the cytokine balance that promote allergic inflammation (Bonini et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotrophins have attracted much interest for their therapeutic potential in a range of neurologic disorders (Schulte-Herbruggen et al 2007). BDNF has also emerged as a potent synaptic modulator involved in many forms of activity-dependent synaptic plasticity (Lu 2003) and may play an important role in learning and memory (Tyler et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has implied the role of p75NTR receptor and its ligands in the regulation and modulation of neurological and behavioral functions [47][48][49] . Some prior reports have also indicated that epilepsy often shows a comorbidity with behavioral disturbances, including aggression and agitation [12,17,43] , and induction of SE by pilocarpine can also provoke seizure-associated behaviors such as aggressive and unsocial responses.…”
Section: Discussionmentioning
confidence: 99%